Findbuch des Bestandes Abt. 109: Ämter Reinfeld, Rethwisch, Traventhal - Pingel, Wulf (Veröffentlichungen des Landesarchivs Schleswig-Holstein, 2010)
This book closes a gap in access to the archival tradition of the Stormarn district. It makes accessible the tradition of the three offices Reinfeld, Rethwisch and Traventhal, which together with the offices Reinbek, Trittau and Tremsbüttel covered approximately the area of today's Stormarn district. It now is kept in the Schleswig-Holstein State Archives and called Department (Abteilung) 109. Until 1867, i.e. up to the beginning of the Prussian era, the lower administrative districts of Schleswig and Holstein were the provincial administrative districts In the dukedoms of Schleswig and Holstein. In simple terms, they can be described as the predecessors of today's administrative districts. The offices had administrative, legal and fiscal responsibilities. The stock of the Dept. (Abt.) 109 which can now be used comfortably with this find book comprises 60 metres of archive material,. It makes over three hundred years of Stormarn's history from the middle of the 16th century to 1867 accessibble. The documents, official records, official and protocol books, as well as the almost complete official accounts document the social and everyday history of the rural population, the mutual relations between town and country, the work of the administration and jurisdiction, the development of services and taxes, but also the effects of armed conflict on the offices. If you would like to know something about these and similar topics of Stormarn's history today, you can find out the relevant archive material by means of a thematic classification system and, in addition, by means of a detailed register of persons, places and subjects.